PENDIDIKAN KARAKTER DALAM PEMBELAJARAN MATEMATIKA PEMBENTUK GENERASI ANTIKORUPSI - Hery Kristanto, Vigih (Widya Warta, 2011)
Education plays an important role in human life. Through education, a country can control the development of human resources quality for a better future. The advantage of education includes both preparing knowledgeable students and building their good character and attitude in society. The responsibility to build students’ character relies not only on the classes of divinity and civics but on the other subjects as well. In other words, all the subjects are responsible of forming students’ character. Can mathematics learning be integrated with education of character?. Is the method capable of solving corruption problems by preparing anti-corruption generation in the future?. The value of character education is integrated with students’ character in Elementary School, so, in mathematics classes, teachers can use some kinds of material to help solve corruption problems.